How do you solve #-(x+2)-2x=-2(x+1)#?
Firstly, you need to get the
#-x - 2 = -2 (x + 1) + 2x#
which can be simplified by expanding the brackets then simplifying
#-x - 2 = -2#
which in turn can be also simplified by adding 2 to both sides, giving you
#-x = 0#
which is the same as
#x = 0#
Hopefully this was helpful...
See the entire solution process below:
First, expand the terms within parenthesis. Take special care to ensure you manage the signs of the individual terms correctly:
We can next group and combine like terms on the left side of the equation:
Now, we can add